A Case Report of Familial Congenital Aniridia and Oculocutaneous Albinism with an Emphasis on Multifaceted and Multidisciplinary Patient Management. - Schwalbe, Rachel; Ross, Nicole (Optometry & Visual Performance, 2022)
Background: Congenital aniridia and oculocutaneous albinism impair ocular development and frequently present with overlapping signs and symptoms. Similar manifestations include foveal hypoplasia, optic nerve hypoplasia, iris abnormalities, congenital nystagmus, strabismus, and decreased visual acuity, which hinder quality of life in affected individuals. Case Report: We present a case of a six-yearold male with both familial congenital aniridia and oculocutaneous albinism yielding secondary visual impairment. His low vision optometric care included refractive error correction, photophobia control, low vision device evaluation, strabismus and amblyopia treatment, ocular health examination and management, and functional vision assessment. The patient's specialty care team included a low vision optometrist, a pediatric glaucoma specialist, a strabismus specialist, a teacher of the visually impaired, an orientation and mobility specialist, and an occupational therapist. Conclusions: The unique contributions of each member of the care team facilitate the holistic development of pediatric low vision patients. Appropriate management, including a multifaceted and multidisciplinary approach to care, is critical to maximize quality of life and visual potential.